On two long lasting delusions in the history of equations - Klukovits, Lajos (Teaching Mathematics and Computer Science, 2011)
Almost everybody was thought, that the 9th century Moshlem mathematician al-Khwarismi was the inventor of two powerful methods – called by him as al-jabr and al-muqabala – in solving quadratic equations. The second belief is that between Leonardo’s Liber abaci and Luca Pacioli’s Summa... happened nothing interesting in algebra. We will show that both beliefs are false by giving examples from the antiquity and analyzing Mediaeval Italian manuscripits.